2015
DOI: 10.3390/w7105437
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Supply of Safe Drinking Water for Underserved Households in Kenya: Investigating the Viability of Decentralized Solutions

Abstract: Water quality and safe water sources are pivotal aspects of consideration for domestic water. Focusing on underserved households in Kenya, this study compared user perceptions and preferences on water-service provision options, particularly investigating the viability of decentralized models, such as the Safe Water Enterprise (SWE), as sustainable safe drinking water sources. Results showed that among a number of water-service provision options available, the majority of households regularly sourced their dome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
4
22
0
Order By: Relevance
“…This finding mirrored an earlier similar finding on the same issue for Nairobi city where some residents were found to spend up to about 11% of their monthly income [73]. A subsequent study by [74] and later by [75] found that Nairobi city has a huge unequal and inequitable consumption of the available conventional water hence forcing residents to rely on water vending. Further, a most recent revelation by [76] showed that only 50% of Nairobi residents receive clean piped water.…”
Section: Water Supply Reliabilitysupporting
confidence: 78%
“…This finding mirrored an earlier similar finding on the same issue for Nairobi city where some residents were found to spend up to about 11% of their monthly income [73]. A subsequent study by [74] and later by [75] found that Nairobi city has a huge unequal and inequitable consumption of the available conventional water hence forcing residents to rely on water vending. Further, a most recent revelation by [76] showed that only 50% of Nairobi residents receive clean piped water.…”
Section: Water Supply Reliabilitysupporting
confidence: 78%
“…Social, commercial and technical innovations can help extend the coverage and institutional creativity needed for future growth [143]. Decentralized planning may reach more people and distribute power to lower levels for creative, innovative and responsive provision programs [144], although others suggest that community management can shift perceptions of responsibility to the more visible local figures [145].…”
Section: )mentioning
confidence: 99%
“…However, it is expected that Kenya's legal framework will soon actively promote and support the adoption of RWH systems [137]. A recent study focusing on underserved households in urban and rural Kenya, investigating the viability of decentralized models, such as the Safe Water Enterprise (SWE), reports that a maximum of 2% of their water supply presently comes from RWH systems [138].…”
Section: Implementation In Developing Countriesmentioning
confidence: 99%
“…Water scarcity is also a real problem in arid and semi-arid (ASAL) regions of Kenya [88,138]. A review of the Australian Centre for International Agricultural Research (ACIAR) activities in Africa concerned with agricultural advances suggest that new skills should be developed through training and longer-term involvement with Australian scientists, implying that information alone is not sufficient and that some projects have been unsuccessful as a result of a lack of underlying skills, the long time taken to learn new techniques, and high turnover of personnel [140].…”
Section: Implementation In Developing Countriesmentioning
confidence: 99%